Monetary policy and stock market valuation - Olli-Matti Laine (Bank of Finland, 2020)
This paper estimates the effect of the European Central Banks's monetary policy on the term structure of expected stock market risk premia. Expected stock market premia are solved using analysts' dividend forecasts, the Eurostoxx 50 stock index and Eurostoxx 50 dividend futures. Although risk-free rates have decreased after the global financial crisis, the results indicate that the expected average stock market return has remained quite stable at around 9 percent. This implies that the expected average stock market risk premium has increased since the financial crisis. The effect of monetary policy on expected premia is analysed using VAR models and local projection methods. According to the results, monetary policy easing raises the average expected premium. The effect is explained by a rise in long-horizon expected premia.
URN:NBN:fi:bof-202009172345
Keywords: E52; G12; 330; Monetary policy; Stock market; Equity premium